O23 A good death isn't a bad thing: time to train for the times. (5th November 2017) - Fernando, Asanga; Snelgrove, H; Minton, O
Abstract : Throughout the history of Simulation Based Learning, the death of an artificial patient has been often viewed as a catastrophic event which can often elicit powerful responses from learners. Often, learners feel that the death of a simulated patient is a reflection of their adverse 'performance' during simulation. This possibly stems from the use of simulation for assessment purposes such as Advanced Life support. As such, the current SBL landscape continues to perpetuate the notion that a death in a simulated environment is an adverse event, despite the increasing amount of evidence highlighting that a good death is an important part of life, and one that can prepared for. Although this is often recognised in simulation involving palliative care clinicians, this does not exist across clinical practice. There has been a paucity of published research into how we train the healthcare workforce using SBL on the importance of a good death. Smith –Stoner highlights the issues training nurses on end of life care. This workshop aims to highlight the need for less stigmatising and more realistic portrayals of end of life care in SBL. Given the fact that a good death is an often inevitable part of care involving healthcare professionals, it also becomes the job of those working in simulation centres and those trained in facilitating SBL to challenge their own perceptions about patient death, and to encourage a move towards better SBL training for healthcare professionals who often confront this important reality in clinical work, including by reducing the 'stigma' associated with a simulated patient death. Learning Objectives: To encourage reflection on how we portray death in simulation and how to move forward in line with curricula and clinical practice to manage the end of life care of patients in a simulated environment, encouraging discussion on how to portray and encourage training towards, a good death. This workshop can accommodate 40 participants in any room format and will rely on the presenters to engage the participants in an interactive manner including small group work as well as exploration of current guidance. The workshop will explore attitudes of the participants and their thoughts on how to overcome stigma in portraying simulated patient deaths.